Automated Hydroponics System for Urban Farming - Inba Rexy*, Siddharth Shiva, Joseph Rajesh, Ganesh Kumar (International Journal of Advanced Science and Technology, 2020)
Hydroponics refers to the process of growing plants without using soil. Instead, a solution of nutrients in water is passed through its roots for their nourishment. We use a vertical, continuous-flow solution culture technique hydroponic system in a controlled environment to grow crops such as spinach. The environmental factors that we controlled include the temperature, lighting, water supply and the pH. We also enabled Internet of Things (IoT) control of the system. This allows for the control of the various parameters in the system from a distance, over the internet. Various crops have various ideal conditions, and these conditions can be changed as required in this system. The system uses the Intel Edison board for its component integration. Furthermore, the system was designed with the aim of allowing for a more efficient use of space, better pest management, and overall increased efficiency with regard to plant growth rate and quality. The system is also meant to be relatively easy to transport, and cost efficiency is a huge bonus, wherein while initial investment may be high, follow up prices are markedly reduced from conventional methods.